Think Trustworthiness, Quality and Value! How the Code of Practice for Statistics supports analysts to use data in a way that builds public confidence - Miller-Bakewell, Helen; Babb, Penny (International Journal of Population Data Science, 2025)
Objectives This presentation will show how the Code of Practice for Statistics, developed and maintained by the Office for Statistics Regulation (OSR), is relevant to anyone working with data, helping them to work in ways that support public confidence in analysis. Methods The Code of Practice for Statistics encourages and supports data sharing and linkage, in a secure way, to maximise the value of data for the public good. It provides a framework for tackling tough questions like: How do I navigate the demands of ethical practices and data governance? How do I balance conducting research with involving and engaging the public? How do I weigh up meeting research goals with serving the public good? Results By using a Think TQV approach – applying the Code framework of Trustworthiness, Quality and Value to your practice – you can work out the appropriate way forward. Trustworthiness helps you work with integrity, building in transparency and ensuring you are accountable, particularly in the ways you handle and share data. Quality challenges you to ensure your data and methods are suitable, respondent-centric and inclusive, and assured. Value prompts you to be active and open in engaging and involving stakeholders and public members in your work, to be responsive to what you hear and to ensure the value of data are maximised. Conclusion All analysts can benefit from applying the Code when working with data. Thinking TQV supports you to improve your practice: to work ethically, to ensure good governance, and to build a fuller insight of how research will serve the public good by involving and engaging the public and other stakeholders.